In-situ methanolysis of Jatropha curcas seeds in Soxhlet extractor - Prabaningrum, N. (Trans Tech Publications Ltd, 2014)
Biodiesel is an alternative fuel to replace petro diesel with some advantages. One of the methods to produce biodiesel is in-situ transesterification. In this study, in-situ methanolysis of Jatropha curcas seeds in Soxhlet extractor was investigated. Normal hexane was added to enhance the solubility and extractability of methanol in the presence of NaOH as catalyst to Jatropha curcas oil. Response surface methodology based on Box Behnken design was used to determine the optimum reaction conditions. The ratio of mixture volume to seed weight (7.5; 12.5), catalyst concentration (1.75; 2.25 wt.) and volume ratio of methanol to mixture (0.3; 0.7) were selected as experimental parameters. The biodiesel yield of (91.37 ± 0.57) , which was insignificantly different with the predicted value, was obtained with the optimum conditions as follows: the ratio of the mixture volume to seed weight of 12.48 (ml/g), 1.75 wt. of sodium hydroxide concentration, 0.31of the ratio of methanol volume to the mixture volume at 60 0C for 60 min reaction time. The maximum yield of (98.63 ± 2.9) was achieved at optimum conditions during 3 hours reaction time at 60°C. © (2014) Trans Tech Publications, Switzerland.